Analysis of root growth in two turfgrass species with minirhizotron and soil coring methods - Young, Jason Scott, author; Qian, Yaling, advisor; Comas, Louise, advisor; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2015)
In this study root growth of a turf-type variety of inland saltgrass (Distichlis spicata L. Greene) (a native grass with varieties in development by Colorado State University) and Kentucky bluegrass (Poa pratensis L.) (a common turfgrass planted in the arid and semi-arid west) was examined under saline conditions in a pot experiment and non-saline conditions in the field. Since turfgrass is a high user of water, the turf industry is interested in using native species that use less water and also salt-tolerant species, which may allow the industry to use marginal water (grey water) for irrigation. However, plants with different root distributions will need to have irrigation managed differently. These experiments examined root growth differences in saltgrass and Kentucky bluegrass to begin exploring how these species might need to be managed differently in saline and non-saline conditions. Two separate experiments were conducted to answer the two objectives of this research: (I) to evaluate root growth of inland saltgrass under saline conditions in a growth chamber and (II) observe unrestricted root growth in the field both over time with a minirhizotron camera system, and in stands of differing age with a soil coring method. In the first experiment, root growth in container grown saltgrass under salt stress showed increased flushes of fine root growth in response to moderate levels of salinity (8 dS/m) compared to the control. Root growth increased about 3 weeks after salt treatments began, suggesting that this time frame was long enough for ionic stress to occur in the shoots root responses were seen. In-growth root tubes placed in the soil of the salt stressed saltgrass showed trends of increasing root and rhizome growth with increasing salt stress, this was opposite the trends seen in Kentucky bluegrass. In experiment II, field-grown saltgrass plots of varying stand age (1, 4, 5, and 8 years) had less root biomass in soil layers less than 30 cm compared to bluegrass. Kentucky bluegrass root biomass was nearly zero below 30 cm, whereas saltgrass had roots down to 275 cm in stands that had been growing longer than 4 years. In soil layers up to 1.8 m, saltgrass root mass was greater with increasing stand age. Minirhizotron observations showed that 15°C was the soil temperature at which root growth began in saltgrass and dramatically slowed in Kentucky bluegrass which had a growth range of 0 to 15°C. When soil temperatures were above 15°C saltgrass roots continued to grow at a slow but steady rate during the summer months. Findings that saltgrass produced roots deeper in the soil profile and was responsive to saline soil may impact where and when it is used. If stored moisture is present deep within the soil, saltgrass has a unique ability to mine this water that would be out of reach of shallower rooted turfgrasses. Deep rooting can also have implications for slope stabilization which can be important in the arid west where bare slopes can be stripped of soil during heavy and infrequent rainstorms. The responsiveness of rooting in saline soils may be the underlying mechanism explaining the enhanced growth of saltgrass under mild saline conditions. Increased surface area from new fine root production can enhance root water uptake providing more water to growing shoots. More studies are needed to explore root responsiveness in many types of plants, including saltgrass, to discover the true benefit of fluctuations in root system architecture.